« De l’Est russophone et russophile à l'Ouest nationaliste et ukrainophone » : la construction des communautés linguistiques ukrainiennes dans la presse française - Alexia Kis-Marck (Lengas)
The conflict in Ukraine has been drawing the international media’s attention  over the last two years. They come forward with different interpretations of the event. One of the readings picked by the French media’s was to portray the country as a state fractured in two irreconcilable ethno-linguistic communities: the ‘pro-Russians’ who are Russian speaking and the ‘pro-Europeans’ who are Ukrainian speaking.  This paper proposes to enlighten the construction of linguistic communities representation by French media and to identify the different criteria used to define these groups formed around the use of a language. What is then the role of the language in this description? What additional elements would be shared by members of these ‘drawn up by the media’ communities? Does the description of these communities matches Ukrainian reality?